PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 008 TALANG PERIGI KECAMATAN RAKIT KULIM KABUPATEN INDRAGIRI HULU - Helni Dlita; Hendri Marhadi; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Absract : The problem in this research is the low level of student learning outcomes caused by the less motivated students, teachers prefer the ability of individual students, teachers use learning lecture model only less attractive to students, teachers guide students' supervising or less while working on the test, and teachers are less rewarding to the students. One of the right learning model in overcoming these problems is to use cooperative learning model (Cooperative Learning) types of Student Team Achievement Divisions (STAD). This research aims to improve the learning results of IPS grade IV SD Negeri 008 Talang Perigi Kecamatan Rakit Kulim Kabupaten Indragiri Hulu. The subject in this study are grade IV SD Negeri 008 Talang Perigi Kecamatan Rakit Kulim Kabupaten Indragiri Hulu with 26 students number of students. This research is a Research Action class (Classroom Actions Research) consisting of 2 cycle. Based on the results of research and data analysis noted that an increase in the percentage of the activity of the teachers earn an average of 82.29% success criteria very well. Implementation cycle II activity for teachers earn an average of 87.5% success criteria very well. Implementation cycle I for the activity of the students gained an average success 77.5% with good criteria. Implementation cycle II for the activity of the students gained an average of 87.5% success criteria very well. Improved student learning outcome of the cooperative learning model applied before type STAD is 64.8 of 26 people who follow Deuteronomy 8 the person completely and 18 students hadn't 30.76% ketuntasan with the percentage with less qualification. At the UH 1 I cycle daily value rose to students who have experienced an increase as much as 69.32 4.52%, with the number of students who complete 18 students. Cycle II experienced an increase in the average value of as much as 11.44% to 80.76. The entire students comprehensively on the implementation of the UH 2 with a percentage of 100%. A class is declared finished when having achieved ≥ 80 from the number of students who achieved the specified KKM is ≥ 70. Thus it can be concluded that cooperative learning model of type Student Team Achievement Devision (STAD) can improve learning outcomes SOCIAL SCIENCE grade IV SD Negeri 008 Talang Perigi Kecamatan Rakit Kulim Kabupaten Indragiri Hulu Keywords: model of learning, the learning results of STAD